2019
DOI: 10.3390/catal9121064
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel Production Using Bauxite in Low-Cost Solid Base Catalyst Precursors

Abstract: Investigation was conducted on bauxite mixed with Li2CO3 as alkali metal catalysts for biodiesel production. Bauxite contains a high percentage of Si and Al compounds among products. Because of the high expense of commercial materials (SiO2, Al2O3) that makes them not economical, the method was very recently improved by replacing commercial materials with Si and Al from bauxite. This is one of the easiest methods for preparing heterogeneous transesterification catalysts, through one-pot blending, grinding baux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A lot of the used waste materials typically contain various alkali metal compounds that act as basic catalysts after calcination of the substance (Pandit and Fulekar, 2019). Many researchers have used waste substances such as spent coffee powder (Nguyen et al, 2020), crab shell (Madhu et al, 2016), egg shell (Santya et al, 2019), fish bone (Tan et al, 2019), waste animal bones (Chingakham et al, 2019), sea shell (Jaiyen et al, 2015), modified bauxite with Li 2 CO 3 (Dai et al, 2019) and ceramics wastes (Dai et al, 2018a) to produce catalysts. Subsequent to calcination of the mentioned substances, they have used active CaO or MgO as the basic catalysts or a base for the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of the used waste materials typically contain various alkali metal compounds that act as basic catalysts after calcination of the substance (Pandit and Fulekar, 2019). Many researchers have used waste substances such as spent coffee powder (Nguyen et al, 2020), crab shell (Madhu et al, 2016), egg shell (Santya et al, 2019), fish bone (Tan et al, 2019), waste animal bones (Chingakham et al, 2019), sea shell (Jaiyen et al, 2015), modified bauxite with Li 2 CO 3 (Dai et al, 2019) and ceramics wastes (Dai et al, 2018a) to produce catalysts. Subsequent to calcination of the mentioned substances, they have used active CaO or MgO as the basic catalysts or a base for the catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the gradual depletion of traditional fossil resources, there has been growing interest in the development of alternative renewable fuels that are easily available and environmentally friendly, for example, biodiesel. [ 1–4 ] Traditionally, biodiesel refers to fatty acid methyl or ethyl ester produced through the (trans)esterification [ 5 ] process of low‐cost raw materials such as waste cooking oil, [ 6 ] jatropha seeds, [ 7 ] palm fatty acid, [ 8 ] and distillate [ 9 ] with methanol or ethanol using acid/alkaline catalysts. [ 10 ] These raw materials contain a high level of free fatty acids (FFAs) resulting in a saponification problem with a homogeneous basic catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Within the field of biodiesel and oleaginous feedstock, Ching-Chang Chen et al present the use of bauxite as a low-cost solid base catalyst precursor for the production of biodiesel via transesterification. Bauxite is economic, contains a high percentage of Si and Al species, and can replace expensive commercial materials [16]. Likewise, Mark Crocker et al have demonstrated the promotional effect of Cu, Fe and Pt on the performance of Ni/Al 2 O 3 in the deoxygenation of used cooking oil to fuel-like hydrocarbons [17].…”
mentioning
confidence: 99%